Quantum spin liquid from electron–phonon coupling - Xun Cai; Zhaoyu Han; Zi-Xiang Li; Steven A. Kivelson; Hong Yao (Proceedings of the National Academy of Sciences, 2025)
A quantum spin liquid (QSL) is an exotic insulating phase with emergent gauge fields and fractionalized excitations. However, the unambiguous demonstration of the existence of a QSL in a “nonengineered” microscopic model (or in any material) remains challenging. Here, using numerically exact sign-problem-free quantum Monte Carlo simulations, we show that a QSL arises in a nonengineered electron–phonon model. Specifically, we investigate the ground-state phase diagram of the bond Su–Schrieffer–Heeger model on a 2D triangular lattice at (one electron per site), which we show includes a QSL phase which is fully gapped, exhibits no symmetry-breaking order, and supports deconfined fractionalized holon excitations. This suggests promising routes for finding QSLs in realistic materials and high- T c superconductivity by lightly doping them.